2009
DOI: 10.1051/0004-6361/200912713
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in the globular cluster NGC 6397

Abstract: Context. Most globular clusters are believed to host a single stellar population. They can thus be considered a good place to study the Spite plateau and to search for possible evolutionary modifications of the Li content. Aims. We want to determine the Li content of subgiant (SG) and main sequence (MS) stars of the old, metal-poor globular cluster NGC 6397. This work was aimed not only at studying possible Li abundance variations but also to investigate the cosmological Li discrepancy. Methods. Here, we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(5 citation statements)
references
References 43 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Li observations have also been performed in some globular clusters. For example, in NGC 6397, González Hernández et al () and Lind et al () found the 7 Li/H values to be (2.34 ± 0.05) × 10 −10 and (1.78 ± 0.04) × 10 −10 , respectively, somewhat higher than the result for field stars, whereas Monaco et al () found a value of 7 Li/H = (1.48 ± 0.41) × 10 −10 in Omega Centauri that is similar to halo star abundances.…”
Section: Introductionmentioning
confidence: 89%
“…Li observations have also been performed in some globular clusters. For example, in NGC 6397, González Hernández et al () and Lind et al () found the 7 Li/H values to be (2.34 ± 0.05) × 10 −10 and (1.78 ± 0.04) × 10 −10 , respectively, somewhat higher than the result for field stars, whereas Monaco et al () found a value of 7 Li/H = (1.48 ± 0.41) × 10 −10 in Omega Centauri that is similar to halo star abundances.…”
Section: Introductionmentioning
confidence: 89%
“…The metal‐poor ([Fe/H]=−2.3 dex) GC M92 shows a mean value of A (Li) = 2.36 ± 0.05 dex, σ= 0.18 (Bonifacio 2002). For NGC 6397 ([Fe/H]=−2.0 dex), different studies point towards A (Li) between 2.25 ± 0.01 (Lind et al 2009a) and 2.30 ± 0.01 dex (González Hernández et al 2009) in stars along the MS or around the TO. The value of A (Li) in nine TO stars of NGC 6752 ([Fe/H]=−1.4 dex) has been measured by Pasquini et al (2005) who found A (Li) = 2.24 ± 0.05 dex (σ= 0.15).…”
Section: Evolution Of A(li)mentioning
confidence: 99%
“…Extensive chemical screenings of the Li content in GC dwarf stars have so far been limited to a few closest objects, such as 47 Tuc (Bonifacio et al 2007; D'Orazi et al 2010), NGC 6397 (Bonifacio et al 2002; Korn et al 2006a; González Hernández et al 2009; Lind et al 2009a), NGC 6752 (Pasquini et al 2005) and M92 (Boesgaard et al 1998; Bonifacio 2002). The metal‐poor GC NGC 6397, in particular, has recently been the object of an intense debate regarding the discrepancy between the cosmological and stellar Li abundance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond this series of papers, studies of lithium in metal-poor stars have provided crucial mass- and metallicity-dependent constraints (González Hernández et al. 2009 , 2019; Meléndez et al. 2010 ; Nissen & Schuster 2012 ).…”
Section: Introductionmentioning
confidence: 99%